Biomass dry matter yield of willow and Miscanthus in low‐input cropping on heavy clay soils in Ukraine. (22nd September 2022) - Prysiazhniuk, Oleh; Maliarenko, Oksana; Roik, Mykola; Fuchylo, Yaroslav; Lewandowski, Iris; Makovskis, Kristaps; Lazdina, Dagnija; von Cossel, Moritz
Abstract: In Ukraine, 6.5 million hectares of agricultural land characterized by heavy clay soil could be available for sustainable bioenergy crop cultivation because they are considered marginal for food crop cultivation. This study investigated the biomass dry matter yield (DMY) of willow ( Salix triandra L. and Salix viminalis L.) and Miscanthus ( Miscanthus × giganteus Greef et Deuter) at two experimental sites with heavy clay in Ukraine. To promote plant rooting and adaptation in the first year of cultivation under low‐input conditions, tillage, moisture‐retaining agents, foliar fertilization, planting density and row spacing were varied. Willow obtained notable DMY on hard clay soils (clay >50%). The variety 'Tora' revealed the best DMY performance, indicated by the highest increment (4.1–4.6 m) in the first year of the second cycle. The highest biomass DMY (28.8 Mg ha −1 ) was obtained at a planting density of 15 000 plants ha −1 and a row spacing of 0.75 × 1.50 m. However, neither willow nor Miscanthus allow for a feasible biomass production at clay contents above 64%, because the young roots are damaged and deprived of nutrients as the soil dries out. For Miscanthus, plowing provided better soil loosening and easier sprouting of rhizomes compared with mini‐till. The application of moisture‐retaining agent Aquasorb (200 kg ha −1 ) supported Miscanthus plants with moisture in the first year of vegetation, but it did not maintain soil moisture in the long term. Therefore, growing willow and Miscanthus on soils with clay contents above 64% is not feasible because the soil texture and tendency to crack significantly reduce the DMY. © 2022 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.